ANALISIS PENGARUH INVESTASI SEKTOR TRANSPORTASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2004 - 2013 - TRI MULYANI SETYOWATI (Institut Transportasi dan Logistik Trisakti, 2015)
This research is conducted to find out how big is the role of foreign direct investment and domestic for economic growth in Indonesia during the period 2004 – 2013 by using static model analysis with Ordinary Least Square regression. The result of the sectoral analysis that foreign direct investment and domestic transportation sector does not influence the Indonesian economic growth . It’s because of risk in country factor, that is small domestic markets that cause lower rate of return and lack of supporting facilities such as infrastructure and transportation, skilled employees, and technology. Factor inhibiting the influx of investment also is a problem of economic instability, political, security and legal certainty.The result of the multi sector analysis that foreign direct investment and domestic for overall sectors of the economy does influence the Indonesian economic growth with using a significance level of 10%. Besides domestic savingshas very strong influence to economic growth both for sectoral and multi sector analysis.